A STUDY ON CONSUMER PREFERENCE AND SATISFACTION LEVEL TOWARDS HALDIRAM’S PRODUCTS WITH SPECIAL REFERENCE TO TIRUPUR CITY - Ms. Bala Arthi S; Mrs. L. Priya , (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study aims to explore the consumer preferences and satisfaction towards Haldiram's products. Haldiram's is one of the leading brands in India's snack food market, offering a variety of traditional and contemporary snack options. The study surveyed 120 respondents across different age groups, genders. The research findings revealed that the taste and quality of the products are the two most crucial factors that influence consumer preferences towards Haldiram's. Further, the packaging, price, and availability of the products were also found to be significant factors affecting consumer preferences.